The Economic Impact of Migrants from Hurricane Maria - Giovanni Peri; Derek Rury; Justin C. Wiltshire (Institute of Labor Economics (IZA), 2020)
Using a synthetic control estimation strategy we examine the economic impact of a large inflow of people from Puerto Rico into Orlando in the aftermath of Hurricane Maria, which devastated Puerto Rico in September 2017. We find that aggregate employment in Orlando increased as a result of the inflow, as did employment in the construction and retail sectors. We also find positive overall employment effects on non-Hispanic and less-educated workers, as well as positive effects on compensation for those same subgroups in the retail sector. In the construction sector – which absorbed the preponderance of this migrant labor supply shock – we find that earnings for non-Hispanic and less-educated (workers likely to be natives) decreased by a modest amount. These results together suggest that, while migrant inflows may have small negative impacts on the earnings of likely-native workers in sectors directly exposed to the labor supply shock, employment and earnings of likely-native workers in other sectors are positively impacted, possibly by increased local demand.
Keywords: F22; J15; J21; J61; 330; migration; natural disasters; local economies